The use of complementary and alternative medicine among people living with diabetes in Sydney - Manya Kiran; Champion Bernard; Dunning Trisha (BMC, 2012)
Abstract Background Complementary and alternative medicine (CAM) is common in patients with chronic disease such as diabetes mellitus. The primary objective of the study was to determine the overall prevalence and type of CAM use in individuals with diabetes mellitus (DM) in Western Sydney and to compare the prevalence and factors associated with CAM use with the literature. Methods A multicenter cross-sectional study was undertaken using a self-completed questionnaire distributed to patients with DM attending a public hospital and specialist endocrinology clinics in the region. The type of DM and pattern of CAM utilisation were analyzed. Results Sixty nine people responded to the questionnaire: age range of 18-75 years during a twelve week collection period. Overall, 32 respondents with diabetes were using some form of CAM, resulting in a utilisation rate of 46.3%. Twenty of the 32 CAM users used CAM specifically to treat their diabetes accounting for 28.9% of the respondent sample population. Multivitamins (40%), cinnamon, Co-enzyme q10 and prayer were the most frequently used CAM modalities. There was no significant difference between males and females, age range, income or diabetes complications between CAM and non-CAM users. (p values each > 0.05) The factor most significantly associated with CAM usage was being born overseas (p = 0.044). Conclusions Almost half the respondents (46.3%) used CAM: 28% used CAM specifically to treat their diabetes. Individuals born overseas were significantly more likely to use CAM than those born in Australia. Other factors such as age, gender, wealth and duration of living with diabetes were not associated with higher rate of CAM usage.